Recent research advances in RNA m5C methylation modification in liver diseases - Chen, Wenjuan; Zhang, Lifan; Gu, Xinyu; Liu, Yafeng; Zhang, Shujun; Hu, Xinjun; Li, Penghui (Frontiers in Molecular Biosciences, 2025)
RNA m5C methylation refers to the process wherein the 5th carbon atom of cytosine in RNA molecules is methylated by the action of methyltransferase, thus forming 5-methylcytosine (m5C). This crucial epigenetic modification significantly impacts gene expression and various biological processes. The abnormal regulation of this process is closely linked to the occurrence and development of various diseases. The liver is the largest digestive metabolic organ, where numerous critical physiological processes take place. Recent studies have emphasized the unique role of m5C modifications in liver physiology and pathology. This review summarizes the common m5C regulatory factors and their functions, with a particular emphasis on the biological roles of m5C RNA methylation regulators in liver injury, liver immunology, viral hepatitis, fatty liver disease, and liver cancer. Furthermore, it compiles findings on m5C regulators and their inhibitors in the treatment and prognosis of liver diseases.